THE USING MIND MAPPING TO IMPROVE ORAL SKILLS IN DAILY ACTIVITIES - M Shobirin; Moh Arifin (FKIP, Universitas Billfath Lamongan, 2022)
The purpose of this study was to determine whether the use of mind maps can improve students' oral skills and to determine the progress of students using mind maps in daily activities. The sample is SMAU BPPT AL FATTAH Siman. To obtain data, researchers conducted pre-experimental research. Researchers conducted pre-test and post-test. Based on the data obtained using r-count and r-table, the number of students is 17, the significance level = 0.05, indicating that the score obtained from the r-table is 0.482, and the r-count is 0.896, so that the r-count is more greater than r-table 0.896 > 0.489, this study is accepted. The results before and after show that mind maps are indeed effective in improving students' abilities, mind maps make students speak English better.